Urban Crime Investigation Association Rules in Istanbul Location of the Perception of the Problem - Bilen, Omer; Okten, Aysenur; Gokalp, Fulya (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2012)
The emerging problems of rapid urbanization in Turkey has caused social, economic and structural transformations in cities since the 1950s. Istanbul is the city most affected by this issue and is the biggest city in Turkey with a population of around 14 million. Also, crime is one of the major problems caused by rapid urbanization. Therefore, it is becoming more crucial to understand the place of crime among all urban problems. In this study, it is aimed to state the problems of the metropolitan areas of Istanbul and determine whether the gender and the distribution of crime in different neighborhoods have an affect on the perception of crime. According to results, the number of problems reported by women is greater than men, and the problems reported in the neighborhoods with high crime rates are greater than the neighborhoods with low crime rates.
Keywords: Association rules; urban problem; crime; crime perception; data mining; Architecture